Optical absorption spectroscopy of reactive oxygen and nitrogen species in a surface dielectric barrier discharge. (26th May 2022) - Schücke, Lars; Bodnar, Arisa; Friedrichs, Niklas; Böddecker, Alexander; Peters, Niklas; Ollegott, Kevin; Oberste-Beulmann, Christian; Wirth, Philipp; Nguyen-Smith, Ryan T; Korolov, Ihor; Gibson, Andrew R; Muhler, Martin; et al.
Abstract: A twin surface dielectric barrier discharge (SDBD) ignited in a dry synthetic air gas stream is studied regarding the formation of reactive oxygen and nitrogen species (RONS) and their impact on the conversion of admixed n-butane. The discharge is driven by a damped sinusoidal voltage waveform at peak-to-peak amplitudes of 8 kVpp –13 kVpp and pulse repetition frequencies of 250 Hz–4000 Hz. Absolute densities of O3, NO2, NO3, as well as estimates of the sum of the densities of N2 O4 and N2 O5 are determined temporally resolved by means of optical absorption spectroscopy using a laser driven broadband light source, suitable interference filters, and a photodiode detector. The measured densities are acquired across the center of the reactor chamber as well as at the outlet of the chamber. The temporal and spatial evolution of the species' densities is correlated to the conversion of n-butane at concentrations of 50 ppm and 400 ppm, measured by means of flame ionization detectors. The n-butane is admixed either before or after the reactor chamber, in order to separate the impact of short- and long-lived reactive species on the conversion process. It is found that, despite the stationary conversion at the selected operating points, at higher voltages and repetition frequencies the densities of the measured species are not in steady state. Based on the produced results it is presumed that the presence of n-butane modifies the formation and consumption pathways of O3 . At the same time, there is no significant impact on the formation of dinitrogen oxides (N2 O4 and N2 O5 ). Furthermore, a comparatively high conversion of n-butane, when admixed at the outlet of the reactor chamber is observed. These findings are discussed together with known rate coefficients for the reactions of n-butane with selected RONS.